Respostas
respondido por:
3
Resposta:
∫x * sen(3x)dx
u=x ==>du=dx
dv = sen(3x) dx ==> ∫dv = ∫ sen(3x) dx ==>v=(-1/3) * cos(3x)
∫x * sen(3x)dx =(-x/3) *cos(3x) -∫(-1/3) * cos(3x) dx
∫x * sen(3x)dx =(-x/3) *cos(3x) +(1/3)*∫cos(3x) dx
∫x * sen(3x)dx =(-x/3) *cos(3x) +(1/9)*sen(3x) + c
estherviana18:
Obrigada
respondido por:
0
Lembrando que:
Agora eu vou chamar:
Vamos substituir isso na formula, obtendo:
=
Resposta:
, ∈ .
Perguntas similares
3 anos atrás
3 anos atrás
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás